Inequality in the distribution of Income and expenditure: an analytical study of a sample of families working in the governmental sectors in the city of Zakho 2016 - Noraldin, Shlair (Humanities Journal of University of Zakho, 2023)
One of the most significant topics the economists and planners focus on is the issue of inequality in the distribution of income and expenses. Because of existing negative influences of inequality and injustice of such a distribution in the society, the current paper tackles the most important numerical and data indicators of the degree of inequality in distributing individual and family income and expenses within governmental sectors (i.e. education, health, finance, etc.) in Zakho City for the year 2016. This has been done by distributing a previously prepared questionnaire among a sample of employers and employees in above mentioned sectors. The delivered copies of this questionnaire were 100 in numbers but 90 of them were returned and they were valid for analysis. The indicators, depending on the questionnaire, used in the paper include Gini Coefficient, Variation Coefficient, Kuznets Index, Thiel Coefficient and Relative Average Deviation. A number of results have been reached out throughout the paper. The most remarkable result is that there is inequality in the distribution of income and expenses between individuals and families. Further, according to the correlations used for measuring the degree of inequality, the individual inequality of income and expenses is higher than that of the family. The Gini Coefficient values were 0.4519 and 0.423 for the individual and family income distributions respectively while the values were 0.40365 and 0.3796 for the individual and family expenses distributions respectively. Such indicators of inequality are due to a number of reasons such as the educational attainment of paterfamilias and the family size. In sum, and according to the results obtained in the paper, a group of suggestions were put to be tacked.